2015
DOI: 10.1007/s00280-015-2721-z
|View full text |Cite
|
Sign up to set email alerts
|

Levels of sirolimus in saliva and blood following oral topical sustained-release varnish delivery system application

Abstract: After an application of sirolimus sustained-release varnish drug delivery system, prolonged drug levels can be achieved in the saliva. The oral topical sirolimus concentrations were potentially therapeutic along with minimal systemic exposure. These results broaden the potential clinical use of sustained-release oral topical rapalogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The authors reported subtherapeutic (~0.2 to 1.1 ng/mL) blood levels and considered the mouthwash safe, since there was minimal passage to blood. A similar study was performed with a sustained-release oral cavity release system, and similar sub-therapeutic blood levels were found in blood [45]. Due to the poor correlations of the drug levels between saliva and blood, salivary TDM does not seem practical at this time.…”
Section: Non-traditional Sample Types For Lc-ms/ms Analysissupporting
confidence: 53%
“…The authors reported subtherapeutic (~0.2 to 1.1 ng/mL) blood levels and considered the mouthwash safe, since there was minimal passage to blood. A similar study was performed with a sustained-release oral cavity release system, and similar sub-therapeutic blood levels were found in blood [45]. Due to the poor correlations of the drug levels between saliva and blood, salivary TDM does not seem practical at this time.…”
Section: Non-traditional Sample Types For Lc-ms/ms Analysissupporting
confidence: 53%
“…In addition to the blood samples for the TDM of ISDs, other potential and convenient specimens, including saliva, hair, and ocular fluids, have also been explored when whole‐blood levels are within the therapeutic range . Belostotsky et al investigated whether a reliable correlation exists between the saliva and whole‐blood TAC levels using an LC–MS/MS method.…”
Section: Chromatography Methodsmentioning
confidence: 99%
“…However, the systemic administration of multiple agents may not be an ideal approach due to significant adverse effects. Local drug delivery provides the flexibility of using different types of delivery systems (e.g., solution for field coverage, patch for limited coverage) or a polymeric system containing multiple agents for the effective management of OSCC, with no/minimal adverse effects . In addition, polymeric local drug delivery systems can be easily tuned for the short‐ and long‐term management of OSCC .…”
Section: Intraoral Site‐specific Chemoprevention Of Oral Cancer: Backmentioning
confidence: 99%
“…Oral solutions/rinses are prepared by dissolving chemopreventive agent(s) in a suitable liquid vehicle or solvent . The drug solution is either painted over the precancerous lesions using a brush/cotton wool or vigorously gargled in the mouth for 2–5 min .…”
Section: Advances In Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation